A broken childhood: The memoir of an Austrian kindertransportee - Ulrika Björk (Nordisk Judaistik)
Review of Lucie Widl (ed. Norbert Götz), From Kindertransport to Postwar Sweden: My Memories. Huddinge: Södertörns högskola, The Institute of Contemporary History / Samtidshistoriska institutet, 2025. 85 pp.